Keanekaragaman Insecta di Persawahan Gampong Limpok Kecamatan Darussalam Kabupaten Aceh Besar Sebagai Referensi Tambahan di Kelas X MAS Darul Hikmah Aceh Besar - Daniah; Ahadi , Rizky; Alija, Rahma (Yayasan Madinah Al-Aziziyah, 2024)
Learning about animal diversity, including insects (arthropods) requires appropriate learning media so that students can be taught to carry out simple identification and determination, especially in class X MAS Darul Hikmah Aceh Besar. This research aims to determine the diversity of insects in the rice fields of Gampong Limpok, Darussalam District, Aceh Besar Regency, determine the results of product feasibility tests resulting from research and the response of class X MAS Darul Hikmah Aceh Besar students to the media that has been produced. The method used in this research is an exploratory survey. Sampling was carried out purportively for insects found at each observation station. Calculating the level of insect diversity uses the Shannon-Weiner index (Ĥ). The parameters in this research include the number of species, number of individuals, level of diversity, environmental physicochemical factors, feasibility tests and student responses. The results of the research show that the level of insect diversity in the rice fields of Gampong Limpok, Darussalam District, Aceh Besar Regency is classified as moderate, namely Ĥ = 1.73, which is in the medium category. The total number of individuals of diurnal insect species in the Gampong Limpok rice fields is 479 individuals, 15 species from 6 orders. The material feasibility test obtained a percentage of 68.85% in the feasible category and the media feasibility obtained a percentage of 76.36% in the appropriate category. The results of student responses obtained a percentage of 95.37% with a very positive category. Based on the research results, it can be concluded that the diversity of insects in the rice fields of Gampong Limpok, Darussalam District, Aceh Besar Regency is classified as moderate, the suitability of the material and media is classified as adequate and the student responses obtained are very positive.